Facilitating closeness between babies with congenital abnormalities and their parents in the NICU: A qualitative study of neonatal nurses' experiences. Issue 15 (8th May 2019) - Skelton, Hannah; Dahlen, Hannah G.; Psaila, Kim; Schmied, Virginia
Abstract: Aims and objectives: This qualitative study explored the experiences of neonatal nurses with facilitating closeness between parents and babies with congenital abnormalities in the neonatal intensive care unit (NICU). Background: Babies with congenital abnormalities often require admission to the neonatal intensive care unit. Parents may experience emotional distancing from their baby, due to their response to their baby's congenital abnormality, as well as physical separation due to their baby's hospitalisation in the NICU. NICU nurses can help facilitate the development of closeness between babies and parents in the NICU. Method: This qualitative interpretive description study involved face‐to‐face, semi‐structured interviews with twelve neonatal nurses following which the data collected were thematically analysed. The consolidated criteria for reporting qualitative research (COREQ) checklist were used in preparing this paper. Results: Three major themes emerged from the analysis—"Everyone copes differently, " "You have to focus on what is the normal thing" and "It's very much an individualised approach." Participants often felt unprepared to care for babies with congenital abnormalities and implemented coping mechanisms to overcome the emotional labour they experienced. Skin‐to‐skin cuddles were considered the most beneficial strategy for parents to develop closeness with their baby. Participants recognised that they sometimes "pushed" parents into engaging with their baby. Participants highlighted the importance of individualised, supportive care for these parents. Conclusions: Neonatal nurses require increased education about congenital abnormalities and individualised care to support them in caring for babies with congenital abnormalities. Relevance to clinical practice: Further research is needed on parental experience of developing closeness with a baby with a congenital abnormality in the NICU.